Analysis of Advertising as a Means of Promoting Goods to the Market ("Journal "U". Economy. Management. Finance.", 2018)
The article describes the definition of advertising. The main tasks, functions and purposes of advertising as a kind of marketing activity are revealed. The main types and sub-types of advertising are identified. The advantages and disadvantages of advertising are described in the work.
Keywords: advertising; marketing; tasks; goals; functions; advantages; disadvantages